WATER-BASED SETTLEMENTS AND THE URBAN PLANNING CHALLENGES IN INDONESIA A CASE STUDY OF BANJARMASIN CITY - Setiadi, Amos; Kusliansjah, Karyadi (PLANNING MALAYSIA, 2021)
The Banjarmasin city is located in territorial waters. The development is currently causing problems related to the context of the aquatic environment. This is because urban development planning is not in accordance with the environmental context. Therefore, this article aims to determine the sustainability of water-based settlements in aquatic environment in Banjarmasin city. This is a qualitative article with the descriptive method used to explain the environmental structure and architectural elements of water-based settlements. Primary and secondary data were obtained from field observations and the city government in the form of maps and pictures of settlements. The data collected were analyzed with the descriptive approach and concluded using the deductive method. This article reveals the form of residence due to community adaptation to water areas and finds that urban spatial development policies need to understand the community’s adaptation process as a local brand of city identity. The concept of ’living with water is a future challenge because it is a water-based cultural adaptation strategy. The architecture of the floating residence has the opportunity to be developed into a floating settlement and city. Therefore, the adaptation of residential architectural forms and environmental structures supports the Banjarmasin city as a waterfront city.